Alternatywność i innowacyjność w edukacji współczesnej – na przykładzie Czech - Zamojska, Eva (Kultura-Społeczeństwo-Edukacja, 2012)
The article in its introduction does present an attempt of facing the dificulties in defining alternativity and innovation in education, taking as the basis opinions of Polish and Czech pedagogists and theoreticians. Second part of the paper is made by a description of examples of alternative and innovative educational activities undertaken in contemporary Czech Republic.